Model Pembelajaran Inovatif Berbasis Teknologi Digital dalam Pembelajaran Sejarah untuk Meningkatkan Keterampilan Abad ke-21 Siswa - Rina Apriana; Putri Sidatillah Umma; Dimas Julian Pratama; Sani Safitri; Rani Oktapiani (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
The development of digital technology in the 21st century has significantly influenced educational practices, including the teaching of history in schools. Conventional teaching methods often make history learning less engaging and limit students’ active participation. Therefore, innovative learning models based on digital technology are needed to improve the quality of history education and support the development of 21st-century skills such as critical thinking, creativity, communication, and collaboration. This study aims to examine the role of innovative digital technology-based learning models in history learning to enhance students’ 21st-century skills. The research uses a qualitative approach with a literature study method by analyzing various academic sources such as books, journal articles, and relevant research publications. The findings indicate that the integration of digital technology in innovative learning models can increase students’ engagement, improve their understanding of historical events, and encourage active learning through interactive media and digital resources. Furthermore, the use of digital technology enables students to access diverse historical sources and develop analytical and interpretative abilities. The study implies that the implementation of digital-based innovative learning models in history education can support more meaningful learning and contribute to the development of students’ competencies needed in the digital era.